EFEKTIVITAS PENGGUNAAN MULTIMEDIA INTERAKTIF DAN MOBILE LEARNING DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA - Mohamad Nurdin, Dadang; Darmawan, Deni; Hernawan, Hudiana (PEDAGOGIA, 2016)
The purpose of this study is (1) to determine the learning outcome of students using interactive multimedia; (2) the improvement of student learning outcomes using mobile learning; (3) to determine the differences between the learning outcome of students using interactive multimedia and mobile learning. The method used is the method of quasi-experimental research design used in this study The Static group pretest – posttest design. Results obtained indicate that (1) there is an increase in student learning outcomes which uses interactive multimedia; (2) there is an increase in student learning outcomes using mobile learning; (3) there are differencesbetween the learning outcome of students using interactive multimedia and mobile learning.